Tinjauan Realitas Terhadap Status, Peran Dan Fungsi Manusia - Mohammad Urfan; Desy Apriani; Dedeh Supriyanti (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2015)
In the letter 12-14 Verse 23 of Qoran, it describes the process of creation of humanfrom nuthfah, turned into alaqah, mudhghah, Izham and khalqan akhar (other beings).Further, It has described in other verses like (QS:25:54), (QS:86:6-7), (QS:18:37),(QS:32:7), (QS: 37:11), (QS:15:26). After learning carefully the various verses above, wecan conclude that the body / physical is one of element that exists within the human.However, these elements have many weaknesses. The purpose of this study was toexamine the three elements that exist in human beings, then we would like to observecarefully about status, role and function of one of the most important elements in humman,which causes humans can be regarded as a perfect creature. The methods of thisobservation is examines various verses in the Qoran related to human, then we would liketo force the reader to trust and believe in the truth. Results of this study prove that humanis composed of three elements, namely the bodies (physical materiality), spirit and soul.The study concluded that soul that distinguishes human from other creatures. The soul thatcan make a human become perfect beings. Soul has been main actors and controllers all ofhuman life in the world.